Producing Amulets of Value in Thai Society - จันทิมา อุดม (Journal of Buddhist Studies Chulalongkorn University, 2018)
Amulets were developed from votive tablets in the image of the Gautama Buddha after His lifetime in order to commemorate the Buddha, the Four Holy Places of Buddhism, to propagate the Buddhist Doctrines, to accumulate good deeds and merits, and to be spiritual anchors for Buddhist people. The conception of votive tablet productions has changed according to different social and historical contexts, culminating in what is known today as “amulets” – collection items of worship with increasing popularity, leading to exchanges and sales which further increased the items’ market and exchange values. These objects of economic value, which have entirely different conceptions and productions from the past, gave rise to the term “Buddhist commerce”. This research finds three problematic areas surrounding the production of amulets in Thai society. They include the formats of amulet production, the assignation of values to amulets, and the control regulations of amulet productions. It proposes that in order to produce amulets of value in Thai society, three main factors need to be given special importance. They include: (1) groups or organizations involved in the production of amulets of value; (2) practical standards for producing amulets of value; and (3) practical guidelines to support the production of amulets of value. These three factors need to be systematically integrated; that is, individuals or groups involved in the production of amulets of value need to foster understanding of and participation in the framework of the production, and they need to act according to the terms of the framework in order to ensure the success of creating a true item of value and worship in Thai society.